2006
DOI: 10.1007/s11095-006-9053-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Solid-State Irradiated Human Insulin

Abstract: Human insulin samples irradiated in the solid-state at 10 kGy (gamma rays) and 14 kGy (electron-beam) meet the European Pharmacopoeia requirements and can be considered as quite stable towards radiation from a chemical analysis viewpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(17 reference statements)
2
4
0
Order By: Relevance
“…The CD profile of insulin in the far UV range is shown in Figure 9. As it is evident from this figure, two minima around 208 and 222 nm, which is typical of predominant α‐helix structure of proteins such as insulin110 that was also reported by other researchers,2, 111 was unaffected by the formulation/process and superimposed almost entirely to that of standard insulin profile. This suggested that the protein maintained its α‐helical structure and hence it's secondary structure and physical stability.…”
Section: Resultssupporting
confidence: 81%
“…The CD profile of insulin in the far UV range is shown in Figure 9. As it is evident from this figure, two minima around 208 and 222 nm, which is typical of predominant α‐helix structure of proteins such as insulin110 that was also reported by other researchers,2, 111 was unaffected by the formulation/process and superimposed almost entirely to that of standard insulin profile. This suggested that the protein maintained its α‐helical structure and hence it's secondary structure and physical stability.…”
Section: Resultssupporting
confidence: 81%
“…Dityrosine formation has been observed previously in insulin upon oxidation with H 2 O 2 /peroxidase [15], metal-catalyzed oxidation with H 2 O 2 /Cu [52], ozone [53], carbon electrodes [54], and exposure to γ-radiation [17]. Inter-molecular dityrosine cross-linking is indicated by two of these studies [15], [52], while carbon electrode oxidation suggests intra-molecular dityrosine cross-linking of insulin [54].…”
Section: Discussionsupporting
confidence: 60%
“…Dityrosine is formed upon radical isomerization followed by diradical reaction, and finally enolization [12], [13]. Dityrosine is found in numerous proteins as a result of aging [13], exposure to oxygen free radicals [13], [14], nitrogen dioxide, peroxynitrite, and lipid hydroperoxides [13], enzymatic reaction with peroxidases [13], [15], [16], γ-irradiation [17], and UV-irradiation [18][20]. In these cases dityrosine cross-linking (C ortho -C ortho ) can be either intramolecular or intermolecular [2], [12], [20] (see Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper on the sterilisation of human insulin, protection of the protein was attempted largely in aqueous solution without resort to either lyophilisation or reduction in temperature (Terryn et al 2007) and can be compared with a previous study by the same author in which solid-state insulin was irradiated at radiosterilisation doses (Terryn et al 2006). At 10 kGy, the recovery of insulin was 96.8%.…”
Section: Sterilisation Of Sensitive Biomolecules In Aqueous Solutionmentioning
confidence: 99%